2013
DOI: 10.1016/j.jneuroling.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of context on word order processing – An fMRI study

Abstract: a b s t r a c tIn languages that have subject-before-object as their canonical word order, e.g. German, English and Danish, behavioral experiments have shown more processing difficulties for object-initial clauses (OCs) than for subject-initial clauses (SCs). For processing of OCs in such languages, neuroimaging experiments have shown more activation in the left inferior frontal gyrus (L-IFG) compared to SCs. The increased activation in L-IFG has been explained in terms of syntactic transformation demands, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
14
2
Order By: Relevance
“…The regions observed for CS are overlapping with those observed in studies of other types of linguistic manipulations, such as semantic integration errors (Christensen and Wallentin, 2011), semantic competition (January et al, 2009;Schnur et al, 2009;Snyder et al, 2007), syntactic complexity (Christensen and Wallentin, 2011;Christensen et al, 2013;Kristensen et al, 2013;Tettamanti et al, 2009), syntactic working memory (Fiebach et al, 2005) and linguistic working memory in general (Kristensen and Wallentin, in press;Wallentin et al, 2006). Wallentin et al (2006) found that Broca's region activity correlated with response time in a working memory task where a visual scene was probed by linguistic cues.…”
Section: Broca's Regionmentioning
confidence: 55%
See 1 more Smart Citation
“…The regions observed for CS are overlapping with those observed in studies of other types of linguistic manipulations, such as semantic integration errors (Christensen and Wallentin, 2011), semantic competition (January et al, 2009;Schnur et al, 2009;Snyder et al, 2007), syntactic complexity (Christensen and Wallentin, 2011;Christensen et al, 2013;Kristensen et al, 2013;Tettamanti et al, 2009), syntactic working memory (Fiebach et al, 2005) and linguistic working memory in general (Kristensen and Wallentin, in press;Wallentin et al, 2006). Wallentin et al (2006) found that Broca's region activity correlated with response time in a working memory task where a visual scene was probed by linguistic cues.…”
Section: Broca's Regionmentioning
confidence: 55%
“…Recently, it has been suggested that activation in this area reflects general linguistic processing costs (Kristensen and Wallentin, in press). In support of this are findings that syntactic manipulations yield increased Broca's region activation (Ben-Shachar et al, 2004;Christensen and Wallentin, 2011;Kristensen et al, 2013;Tettamanti et al, 2009) and findings showing that Broca's region responds to unpredicted word order, rather than syntactic manipulations per se, as defined by working memory demands (Fiebach et al, 2005), cloze probability (Obleser and Kotz, 2010) or context (Kristensen et al, in press). …”
Section: Broca's Regionmentioning
confidence: 86%
“…One suggestion has been that activation in Broca's region reflects general linguistic processing costs (Kristensen & Wallentin, 2015), i.e., that whenever a linguistic process for some reason is difficult or challenged, it causes Broca's region to become more active. In support of this hypothesis are well-known findings that syntactic manipulations yield increased Broca's region activation (Ben-Shachar, Palti, & Grodzinsky, 2004;Christensen & Wallentin, 2011;Kristensen, Engberg-Pedersen, Nielsen, & Wallentin, 2013;Tettamanti et al, 2009) and findings showing that Broca's region responds to unpredicted word order, rather than syntactic manipulations per se, as defined by working memory demands (Fiebach, Schlesewsky, Lohmann, VonCramon, & Friederici, 2005;Wallentin, Roepstorff, Glover, & Burgess, 2006), cloze probability (Obleser & Kotz, 2010) or context (Kristensen, Engberg-Pedersen, & Wallentin, 2014). Broca's region activation is also routinely observed in the absence of word order manipulations (Fedorenko, Duncan, & Kanwisher, 2013;Novick et al, 2010).…”
Section: Broca's Regionmentioning
confidence: 79%
“…Both studies show that the discourse context affects sentence processing in the brain. However, so far, to our knowledge, no neuroimaging experiment has found an interaction between discourse context and word order, neither for Danish, nor for other languages (see Discussion section for a description of a recent null result by Kristensen et al, 2013).…”
Section: Context Affects Behavioral Measures For Word Order Processingmentioning
confidence: 86%